Representation of Women in Making Decisions in Batak Families, Pasaman Regency (Gender Case Study in Binubu Baru Village) - Rosmalina, Rosmalina; Jailani, Muhammad (IHSA Institute, 2024)
In Pasaman Regency, West Sumatra, gender equality remains a significant challenge, particularly in family decision-making processes. This research focuses on understanding women's roles and their representation in decision making within Binubu Baru Village. Despite prevalent patriarchal norms that often marginalize women, this study explores how women engage in decision-making, the factors influencing their choices, and their overall involvement in family decisions. Emphasizing the ideal of horizontal relationships between married couples where no partner is considered superior—the research aims to highlight the importance of equality and mutual support within family units. By examining these dynamics, the study seeks to identify key elements affecting women's participation and contribute to strategies for enhancing gender equality and family well-being